COVID‐19‐related fears and information frequency predict sleep behavior in bipolar disorder. Issue 9 (19th August 2021) - Fellendorf, Frederike T.; Reininghaus, Eva Z.; Ratzenhofer, Michaela; Lenger, Melanie; Maget, Alexander; Platzer, Martina; Bengesser, Susanne A.; Birner, Armin; Queissner, Robert; Hamm, Carlo; Pilz, Rene; Dalkner, Nina
Abstract: Introduction: The coronavirus disease (COVID‐19) pandemic and consequent restrictions including social distancing had a great impact on everyday life. To date, little is known about how the restrictions affected sleep, which is commonly disturbed in bipolar disorder (BD). The aim of this study was to elucidate sleep patterns during the pandemic in Austrian BD individuals. Methods: An online survey assessed sleep with the Pittsburgh Sleep Quality Index (PSQI) and COVID‐19‐associated attitudes, fears, and emotional distress of 20 BD individuals and 19 controls (HC) during the pandemic. The survey was conducted in April 2020, when very strict regulations were declared, and repeated in May, when they were loosened. Results: Individuals with BD reported overall poor sleep according to PSQI sum at both time points. Subjective sleep quality, sleep latency, daytime sleepiness, and PSQI sum were worse in individuals with BD than in HC. Individuals with BD informed themselves more frequently about pandemic‐related topics. Higher information frequency and more COVID‐19 fears (about the virus, own infection, contracting others) correlated with worse PSQI values. Regression models found in BD group that higher information frequency as well as higher COVID‐19 fears in April predicted worse sleep characteristics in May, in particular subjective sleep quality, sleep duration, sleep efficiency, and daytime sleepiness. Conclusion: As sufficient sleep duration and quality are essential for well‐being and particularly important for vulnerable BD individuals, it is important that information about the pandemic is gathered to a reasonable extent and mental health professionals include COVID‐19‐related fears when currently treating BD. Abstract : The online survey showed that individuals with bipolar disorder (BD) reported overall poor sleep in comparison with healthy controls during total lockdown due to the COVID‐19 pandemic as well as when restrictions were loosened. Individuals with BD informed themselves more frequently about pandemic‐related topics and higher information frequency and more COVID‐19 fears (about the virus, own infection, contracting others) correlated with worse sleep. Regression models found in BD group that higher information frequency as well as higher COVID‐19 fears in April predicted worse sleep characteristics in May, in particular subjective sleep quality, sleep duration, sleep efficiency, and daytime sleepiness.